2014
DOI: 10.15252/embr.201438850
|View full text |Cite
|
Sign up to set email alerts
|

Cezanne (OTUD7B) regulates HIF‐1α homeostasis in a proteasome‐independent manner

Abstract: The transcription factor HIF-1α is essential for cells to rapidly adapt to low oxygen levels (hypoxia). HIF-1α is frequently deregulated in cancer and correlates with poor patient prognosis. Here, we demonstrate that the deubiquitinase Cezanne regulates HIF-1α homeostasis. Loss of Cezanne decreases HIF-1α target gene expression due to a reduction in HIF-1α protein levels. Surprisingly, although the Cezanne-regulated degradation of HIF-1α depends on the tumour suppressor pVHL, hydroxylase and proteasome activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 47 publications
(59 reference statements)
5
84
1
Order By: Relevance
“…Flag-Myc-OTUB1, Flag-Myc-OTUB2, Flag-Myc-OTUD3, Flag-Myc-OTUD4, Flag-Myc-OTUD5, Flag-Myc-OTUD6A, Flag-Myc-OTUD6B, Flag-Myc-OTUD7A and Flag-Myc-OTUD7B constructs have been described previously 31 . The HA-GβL(K305R), HA-GβL (K313R), HA-GβL(K305R/K313R) (KRKR), HA-GβL(P265A/E267A) (PEAA), Flag-Myc-OTUD7B(C194A) mutants 29,32 were constructed using the Site-Directed Mutagenesis Kit (Stratagene) following the manufacturer’s instructions. His-Ub, His-Ub(K6R), His-Ub(K11R), His-Ub(K27R), His-Ub(K29R), His-Ub(K33R), His-Ub(K48R), His-Ub(K63R), His-Ub(K0), His-Ub(K48) only and His-Ub(K63) only vectors were provided by P. P. Pandolfi (Beth Israel Deaconess Medical Center, Harvard Medical School).…”
Section: Methodsmentioning
confidence: 99%
“…Flag-Myc-OTUB1, Flag-Myc-OTUB2, Flag-Myc-OTUD3, Flag-Myc-OTUD4, Flag-Myc-OTUD5, Flag-Myc-OTUD6A, Flag-Myc-OTUD6B, Flag-Myc-OTUD7A and Flag-Myc-OTUD7B constructs have been described previously 31 . The HA-GβL(K305R), HA-GβL (K313R), HA-GβL(K305R/K313R) (KRKR), HA-GβL(P265A/E267A) (PEAA), Flag-Myc-OTUD7B(C194A) mutants 29,32 were constructed using the Site-Directed Mutagenesis Kit (Stratagene) following the manufacturer’s instructions. His-Ub, His-Ub(K6R), His-Ub(K11R), His-Ub(K27R), His-Ub(K29R), His-Ub(K33R), His-Ub(K48R), His-Ub(K63R), His-Ub(K0), His-Ub(K48) only and His-Ub(K63) only vectors were provided by P. P. Pandolfi (Beth Israel Deaconess Medical Center, Harvard Medical School).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the K11-linkage-specific DUB Cezanne (OTUD7B) (Bremm et al, 2010;Mevissen et al, 2013) regulates stability of the transcription factor HIF-1α (Bremm et al, 2014) and expression levels of HIF-2α (Moniz et al, 2015). However, in this context, the exact topology of the ubiquitin signal is not yet understood.…”
Section: K11 Linkages In Heterotypic Ubiquitin Conjugates -A Powerfulmentioning
confidence: 99%
“…5 However, in some situations, this process can be reversed by Cezanne-a deubiquitinating cysteine protease that can remove polyubiquitin chains from HIF1α and other proteins. 6 Our study revealed that Cezanne was induced by disturbed flow, and loss-of-function approaches (siRNA, dominant-negative) revealed that it is essential for HIF1α protein expression under these conditions. Cezanne reduced the abundance of high molecular weight forms of HIF1α and coprecipitating polyubiquitin under conditions of disturbed flow suggesting that it stabilizes HIF1α via deubiquitination.…”
mentioning
confidence: 67%